2020
DOI: 10.26803/ijlter.19.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy Development Trends in the Professional Environment

Abstract: This article describes the impact of digital literacy on the professional environment, which allows people to create and share digital content. It also describes how digital literacy can be used communicate and solve problems for effective and creative selfrealization in education, work and social. There are 3 models of digital skills that are largely mutually complementary: DigCompEdu 2018, EU DigComp and Target Competency Model 2025. These models describes changes in the working conditions and requirements f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 15 publications
2
24
0
1
Order By: Relevance
“…It can be summarized that the instructional processes with self-directed learning can promote the learners to have more self-learning experiences, more digital literacy skills, and more achievement. This is in line with the research of Kateryna et.al [24], who said that the digital literacy can be used to communicate and solve problems for effective and creative self-realization in education, work, and society. It is also consistent with the research of Gamage et al [25], saying that the application of interactivity and collaboration in their instructional design can promote skills in learning.…”
Section: -500supporting
confidence: 88%
“…It can be summarized that the instructional processes with self-directed learning can promote the learners to have more self-learning experiences, more digital literacy skills, and more achievement. This is in line with the research of Kateryna et.al [24], who said that the digital literacy can be used to communicate and solve problems for effective and creative self-realization in education, work, and society. It is also consistent with the research of Gamage et al [25], saying that the application of interactivity and collaboration in their instructional design can promote skills in learning.…”
Section: -500supporting
confidence: 88%
“…However, if educators and students want to wholly benefit from media implemented in their learning process, they need to embrace their analytical and critical abilities to become media literate. Modern scholars have defined media literacy as a combination of knowledge and skills necessary for people to orient themselves in an information-based environment, search and share information, interact with other people and computer software, create safe and reliable media content, filter the media content, and solve cognitive tasks (Andriushchenko et al, 2020;Hatlevik et al, 2015). Analysis of recent scientific sources has shown that media literacy deals with the leveling of artificially created information structures and understanding of the principles of their creation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The students communicate with AI then make a written text based on their conversation as a new learning experience. It supported Kateryna et al (2020) that the application of AI technique can enhance digital education quality.…”
Section: Cmc Artificial Intelligence Plays a Significant Role In Enha...mentioning
confidence: 75%